COVID-19 transmission in dental and oral/maxillofacial surgical practice during pandemic: questionnaire survey in 51 university hospitals in Japan. (July 2022) - Tanaka, H.; Kurita, H.; Shibuya, Y.; Chikazu, D.; Iino, M.; Hoshi, K.; Kobayashi, W.; Yokoo, S.; Kawano, K.; Mitsudo, K.; Miyazaki, A.; Ota, Y.; et al.
Summary: Background: The coronavirus disease 2019 (COVID-19) pandemic has become a major public health problem. Dental procedures that generate aerosols are considered to impose a high risk of infection; therefore, dental professionals, such as dentists and dental hygienists, may be at high risk of viral transmission. However, few studies have reported COVID-19 clusters in dental care settings. Aim: To investigate whether dental and oral/maxillofacial procedures are associated with the occurrence of COVID-19 clusters and measures taken to prevent nosocomial infection in dental clinics. Methods: An online questionnaire survey on clinical activities (administrative control), infection control measures (environmental/engineering control, personal protective equipment, etc.), and confirmed or probable COVID-19 cases among patients and clinical staff was administered to the faculties of the dental and oral/maxillofacial surgical departments of university hospitals. Findings: Fifty-one faculty members completed the questionnaire. All members were engaged in the treatment of dental and oral surgical outpatients and actively implemented standard precautions. Fourteen faculty members treated patients with COVID-19, but no infections transmitted from the patients to the medical staff were observed. In seven facilities, patients were found to have the infection after treatment (medical staff came in close contact), but there was no transmission from patients to medical staff. Four facilities had medical staff with infections, but none of them exhibited disease transmission from staff to patients. Conclusion: COVID-19 clusters are unlikely to occur in dental and oral surgical care settings if appropriate protective measures are implemented.